A concatenated multi-dimentional signal modulation transmitter and receiver system and a method thereof - Mohd Ali, Borhanuddin; Khatun, Sabira; Bilfagih, Syed Mohamad Jamalullil; Noordin, Nor Kamariah; Al-Azzo, Wisam Fahmi (2010)
A concatenated multidimensional signal modulating transmitter and receiver system is provided wherein the multidimensional signal modulating transmitter system includes an outer Quadrature Amplitude Modulation (QAM) Modulator, a complex signal splitter connectable to the QAM modulator, two orthogonally split signals connectable to the QAM modulator, two orthogonally split signals connectable in parallel to the complex signal splitter, two dc-offset units are each connectable to two orthogonally split signals, two inner digital modulators connectable to two dc-offset units, wherein the two inner digital modulators are connectable to a parallel to serial converter for transmission on a selected frequency band. The multidimensional signal modulating receiver system includes a serial to parallel converter, two inner digital demodulators connectable to the serial to parallel converter, two dc-offset units connectable in parallel to two inner digital demodulators, a real-to-complex valued converter connectable to two dc-offset units wherein the real-to-complex valued converter is further connectable to an outer QAM demodulator to recover the original transmitted datastream.